Laberinto educativo y aprendizaje fake: Tenemos que hablar - Albarrán Gutiérrez, Álvaro (Journal of Teaching and Learning, 2025)
This book review discusses Ramón Espejo Romero's latest publication, a volume that surveys the educational crisis that Spanish public education currently faces. The review situates the book in a larger trend of publications that have recently emerged to contest the current state of affairs in Spanish primary, secondary, and higher education. It provides an overview of the volume's contents, highlighting its contributions to the current academic debate and its approach to the challenges that beset public education not only in Spain but also in the broader Western world. In so doing, the review underscores the volume's interest for a wide international (albeit Spanish-speaking) audience--an audience concerned with the gradual deterioration of academic standards in public settings, and committed to the need to reclaim a high-quality, affordable, and all-inclusive public education for all.